Assessment of anthropometric measurements and body composition of selected beginner South West Ethiopian soccer players - Esayas Haılu; Daniel Kıbret (Türk Spor ve Egzersiz Dergisi)
This study attempts to determine the anthropometric measurement and body composition quality of south west Ethiopian beginner soccer players’ considering playing position. In so doing, three soccer teams were selected by employing a cluster sampling techniques that consisted of a total forty eight players, and those who attended less than seventeen years of age. Depending on their playing position players were classified in to four categories as goalkeeper (GK), defense (DF), midfielder (MF) and striker (SK). To achieve the stated purpose, cross sectional descriptive research design was employed. The international Society for the Advancement of Kinanthropometry (ISAK) protocol was considered to measure the following anthropometric variables :weight measurements, n_/1; girths, n_/10; lengths, n_/6, skin folds, n_/2;(body fat% and lean mass)and body mass index n-1.The data was analyzed by SPSS version 19, moreover, the level of significance was set at (P lt;0.05). The finding of this study depicted that significant difference of anthropometric measurement among players based on their playing position. DF players possess larger lower limp, interior body and upper limp girth. Whereas, SK player exhibited smaller lower limp, interior body and upper limp girth. In lower limp length GK and SK have larger lower limp length but in upper limp GK possess greater. GK (176.6cm) are taller than all other players of team while MF (170cm) is sorter in overall body height. There is no significant difference in BMI(GK 19, DF 20.4, MD 18 and SK 18), lean mass and body fat% But GK(64.2 kg) are heavier while SK (58kg) lighter in their weight. Whereas, DF (60.7 kg) and MF (60 kg) players are average in their weight. It is found that mean anthropometric measurement of south west Ethiopian youth soccer players was slightly lower than that of top world class players of similar age group players. It is also obtained that lack of significant differences among playing positions reflect on BMI, lean mass and body fat% indicate as coaches are not give playing position specific training for players. In this study, within-position variation was quite large in some cases, which could indicate that a team that does not have the opportunity to hand-pick players, based on anthropometric characteristics, may be at a disadvantage therefore the respective soccer coaches, sport science professionals should take into account the principle of morphological optimization in talent detection, identification and selecting soccer players.